Motivation to COVID-19 Vaccination and Reasons for Hesitancy in Employees of a Czech Tertiary Care Hospital: A Cross-Sectional Survey - Štěpánek, Ladislav; Janošíková, Magdaléna; Nakládalová, Marie; Štěpánek, Lubomír; Boriková, Alena; Vildová, Helena (Vaccines, 2021)
High vaccination coverage among healthcare workers (HCWs) is crucial for managing the COVID-19 pandemic. The aim was to determine the demand for vaccination among all employees (n = 4553) of a tertiary care hospital after several weeks of the vaccine's availability, and to analyze motives for acceptance and reasons for hesitancy through an anonymous online questionnaire. Upon the completion of data collection, the hospital's vaccination coverage was at 69.8%. A total of 3550 completed questionnaires were obtained (2657 from vaccinated, 893 from unvaccinated employees). Significant predictors of vaccine acceptance were: age (odds ratio (OR) 1.01, 95% confidence interval (CI) 1.01-1.02), sex (OR (females) 0.58, 95% CI 0.45-0.75), job type (OR (non-physician HCWs) 0.54, 95% CI 0.41-0.72; OR (non-HCWs) 0.51, 95% CI 0.37-0.71), fear of COVID-19 (OR 1.4, 95% CI 1.34-1.46), history of COVID-19 (OR 0.41, 95% CI 0.34-0.49) and of influenza vaccination (OR 2.74, 95% CI 2.12-3.57). The most frequent motive for acceptance was the effort to protect family members (84%), while concerns about vaccine safety and side effects (49.4%), followed by distrust in the vaccine's efficacy (41.1%) were the top reasons for hesitancy. To increase vaccination coverage among HCWs, it is necessary to raise awareness of vaccine safety and efficacy.